Malnutrition in orthopaedic trauma outcomes (MOTO): orthopedic trauma patients can be effectively screened and stratified for risk of malnutrition using prealbumin. A preliminary outcome study - Anna Jacques, DO; Timothy Niedzielak, DO; Samuel G. Eaddy, DO; Radleigh Santos, PhD; Stacey L. Tannenbaum, PhD, RDN; Joel Rush, DO; Emily Keener, DO; William Neway, III, DO; Bradley Roth, DO; Edward Perez, MD; Brian J. Cross, DO (OTA International)
Abstract. Objectives:. To evaluate prealbumin (PAB) as a prognostic indicator for early detection of malnutrition risk upon admission and its correlation with in-hospital complications and length of stay (LOS) in patients with orthopedic trauma. Methods:. Design:. Retrospective cohort. Setting:. Urban academic Level 1 trauma center. Patients/Participants:. One hundred fifty-eight patients aged 18 years or older with acute traumatic fractures indicated for primary surgical fixation between 2019 and 2022 were included. Serum laboratory tests consisting of PAB, C-reactive protein, complete blood counts, and complete metabolic panel were obtained within 24 hours of arrival. Outcome Measures and Comparisons:. Primary outcome measures included characterization of patient risk factors for increased intensive care unit LOS, hospital LOS, and in-hospital complications. Secondary outcome measures included characterization of patients who were stratified as “at risk” for malnutrition by PAB < 20 mg/dL and identification of complication predictors. Results:. Fifty-one (32%) patients were stratified as “at risk” for malnutrition based on serum PAB < 20 mg/dL drawn within 24 hours of arrival. These patients had longer median hospital LOS (P < 0.001), were more likely to stay in the hospital longer than 7 days (P < 0.009) and >14 days (OR = 3.20, 95% CI 1.17–9.07, P < 0.001), and had twice the amount of postoperative complications during their hospital stay (P = 0.04) than patients with PAB ≥ 20 mg/dL. Conclusions:. Patients with orthopaedic trauma can reliably and cost-effectively be screened and stratified for risk of malnutrition using PAB drawn with immediate admission labs. Level of Evidence:. Level III.